2010
DOI: 10.1260/0144-5987.28.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Denoising of Well Logs and its Geological Performance

Abstract: Well logs play a very important role in exploration and even exploitation of energy resources, but they usually contain kinds of noises which affect the results of the geological interpretation of them. It is common knowledge that wavelet transform does better than Fourier transform in noise removal and suppression of such non-stationary signals as logging signals. However, there are variable choices of the parameters such as the wavelet basis (mother wavelet function), the thresholding rule and the decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…The signals in wireline logs include high-frequency, medium-frequency, and low-frequency components. The low-frequency and medium-frequency components are mostly useful signals (Chen et al., 2018; Honorio et al., 2012; Yu et al., 2010). In contrast, the high-frequency component is mostly noise.…”
Section: Pcr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The signals in wireline logs include high-frequency, medium-frequency, and low-frequency components. The low-frequency and medium-frequency components are mostly useful signals (Chen et al., 2018; Honorio et al., 2012; Yu et al., 2010). In contrast, the high-frequency component is mostly noise.…”
Section: Pcr Modelmentioning
confidence: 99%
“…At present, many methods have been proposed to improve the reconstruction reliability and accuracy of wireline logs. One method uses filtering or multiscale wavelet analysis (MWA) to denoise wireline logs (Chen et al., 2018; Honorio et al., 2012; Yu et al., 2010). Others use histogram calibration to improve the lateral comparability of logs since logging instruments and logging environments are not often the same (Quartero et al., 2014; Ren et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the energy of the useful signal concentrates on fewer wavelet coefficients with bigger amplitudes (Yu et al, 2010). This disbalance between the energy of the components can be measured by the Shannon entropy (Katul and Vidakovic, 1995).…”
Section: Choice Of Wavelet Basismentioning
confidence: 99%
“…They reported that the scheme of image fusion combining WT with the classification of these images is efficient to outline geophysical targets on shallow surfaces. Yu et al (2010) demonstrated that WT is efficient in the process of noise suppression in well logs. In addition, they found that denoised acoustic well logs are superior to the original data when it comes to geological information, such as the identification of layers containing gas.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these existing problems and difficulties, the various physical rock parameters provided by logging data can be considered advantageous for studying the formation of multilevel cyclical deposits. Such logging data contain abundant geologic information with relatively high resolution and good continuity (Serra, 1992;Yu et al, 2010). The ultimate goal is to interpret this geologic information with maximum precision and objectivity.…”
Section: Introductionmentioning
confidence: 99%